Characterization of the Kinematic Evolution of the Hongshiyan Landslide Using the Material Point Method - Yang, Yue; Wang, Rubin; Xu, Weiya; Wang, Yunzi; Yan, Long (Frontiers in Physics, 2022)
In 2014, a landslide disaster occurred at Hongshiyan in Ludian County, Yunnan Province, China, causing the landslide-dames in Niulanjiang River. Scholars have studied the characteristics and causal mechanisms of this landslide and obtained substantial results. However, the kinematic evolution characteristics of the landslide remain relatively unclear. To resolve this problem, we introduced the Material Point Method (MPM)to study large-scale deformations for simulation analysis. We analyzed the variations in the velocity and displacement fields during the movement of the Hongshiyan landslide to reveal its kinematic evolution features. The effects of the internal friction angle, cohesion, and friction coefficient on the characteristics of the landslide movement in alpine valley areas were explored through sensitivity analysis. The results showed that the maximum average velocity of the slide body was 19.52 m/s, occurring at 25 s, the maximum displacement was closely related to the elevation, and the trailing edge of the slide body had the longest runout distance. The deposition morphology of the landslide dam calculated numerically agreed well with the field survey results. The internal friction angle and friction coefficient significantly affected the kinematic characteristics of the Hongshiyan landslide.